Application of a Hybrid SPH - Boussinesq model to predict the lifecycle of landslide-generated waves. (1st March 2021) - Lin, Chuan; Wang, Xiangyu; Pastor, Manuel; Zhang, Ting; Li, Tongchun; Lin, Chaoning; Su, Yan; Li, Yixuan; Weng, Kailiang
Abstract: Landslide-generated wave (LGW) events are particularly dangerous as they are associated with a high risk of loss of life and severe economic damage. The lifecycle of a LGW can be decomposed into various distinct stages, such as generation and propagation. The modeling of the entire LGW lifecycle through the use of a single model is difficult as the hazard characteristics of LGWs differ widely across spatial and temporal scales. Therefore, this study proposed a Hybrid Smoothed Particle Hydrodynamics (SPH) - Boussinesq model to overcome the limitations of individual models and to acquire a more reliable method of analyzing LGWs. An SPH two-layer depth-integrated model was combined with a Boussinesq model (FUNWAVE) through the implementation of a transformation zone. The proposed hybrid model was then applied within the evaluation of the potential risk for the generation of LGWs by impulsive waves generated by the Halaowo Landslide in Jinsha River, China. This study provides a discussion of the process for predicting waves and generated a risk map according to the reference emergency response plan. Highlights: The process of landslide-generated waves is briefly decomposed into generation and propagation stages according to their physical characteristics. A SPH two-layer depth-integrated model, providing a reasonable compromise between computational cost and accuracy, is applied to capture the generation stage of waves induced by landslide. A Boussinesq model capable of solving many coastal processes such as: nearshore wave propagation & transformation, is practiced to investigate the wave propagation problems in river basin areas. A transformation zone is implemented to deliver the physical features of impulsive waves from the near filed to the far field. The proposed hybrid model is then applied to evaluate the potential tsunami risk of a river basin threaten by the probable failure of a nearshore slope.